2021
DOI: 10.1007/s11259-021-09830-2
|View full text |Cite
|
Sign up to set email alerts
|

Cypermethrin and ivermectin resistance in field populations of Rhipicephalus sanguineus sensu lato (Latrielle, 1806) collected from dogs in south India

Abstract: The abuse of acaricides for control of Rhipicephalus sanguineus sensu lato ticks led to a strong selection pressure for acaricide resistance. Data on acaricide resistance in R. sanguineus s.l. populations from India is meager though veterinarians frequently report treatment failures. The present study was aimed to characterize the level of resistance in R. sanguineus s.l. against most commonly used drugs, cypermethrin and ivermectin in Andhra Pradesh, south India. Fourteen adult female tick populations were co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The RR of brown dog ticks to ivermectin in this study was similar to those recorded in Brazil (RR = 1.54–2.97) and India (RR = 1.16–4.79) [ 16 , 29 ] but lower than those recorded in Mexico (RR ≤ 30.5) and Argentina (RR = 1–18.33) [ 15 , 30 ]. These differences in resistance might be related to the frequency of acaricide exposure in each region.…”
Section: Discussionsupporting
confidence: 83%
“…The RR of brown dog ticks to ivermectin in this study was similar to those recorded in Brazil (RR = 1.54–2.97) and India (RR = 1.16–4.79) [ 16 , 29 ] but lower than those recorded in Mexico (RR ≤ 30.5) and Argentina (RR = 1–18.33) [ 15 , 30 ]. These differences in resistance might be related to the frequency of acaricide exposure in each region.…”
Section: Discussionsupporting
confidence: 83%
“…The addition of BA to cypermethrin resulted in a synergistic effect with an LC 50 of 0.16 mL/L, whereas the LC 50 of cypermethrin alone was 1.78 mL/L. Similarly, Sunkara et al (2022) and Rodriguez‐Vivas et al (2017) found cypermethrin resistance in R. sanguineus populations obtained from dogs in South India and Mexico, respectively. Amrutha et al (2021) also reported resistance to deltamethrin in populations of R. sanguineus in South India.…”
Section: Discussionmentioning
confidence: 83%
“…27 Resistance developed by this ixodid to ivermectin was evidenced in Mexico, 28 and also in India, in addition to the fact that resistance to Deltamethrin and Cypermethrin was also observed in this country. 4,29 In view of this, an alternative measure to synthetic chemical acaricides, to be added to a rational integrated system of ticks control measures, 50 is the development of anti-tick vaccines. There are vaccines on the market (Bm86) with antigens related to intestinal membrane proteins of the cattle tick, however, they have low lethality at adult stages (20-30%) and are still costly for the producer.…”
Section: Resultsmentioning
confidence: 99%
“…Brazil, Uruguay, Argentina, Chile, Mexico, United States, Portugal, Spain, Italy, France, Switzerland, Mozambique, India, among others countries. [1][2][3][4] Despite parasitizing mainly domestic dogs, being the most prevalent tick on these hosts in urbanized areas of Brazil and other American countries, this ixodid can, however, parasitize other mammals, birds and reptiles, which partly explains its wide dispersion. [5][6][7] Different strains of R. sanguineus complex are involved in the transmission of various pathogens to their hosts, such as Babesia canis, B. gibsoni, B. caballi, Ehrlichia canis, Hepatozoon canis, Haemobartonella canis, Theileria equi, and Rickettsia spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation